PENGEMBANGAN BAHAN AJAR BERNUANSA ETNOMATEMATIKA DENGAN PERMAINAN TRADISIONAL DAM-DAMAN DALAM MEMAHAMI MATERI GARIS DAN SUDUT - Imalia, Uzdlifatul; Putra, Eric Dwi; Panglipur, Indah Rahayu (Universitas Insan Budi Utomo, 2022)
This study aims to produce Handout teaching materials with ethnomathematical nuances through the traditional game of Dam-daman in understanding line and angle material viewed from the aspects of validity, practicality, and effectiveness. This study uses the Plomp development model which is modified into 4 stages including preliminary investigation, design, realization/construction, and tests, evaluation and revision (test, evaluation and revision). The instruments used include (1) validation sheets, (2) handout implementation observation sheets, (3) student response questionnaires, and (4) test questions. The subjects of this study were 16 students of class VII-E at SMP Negeri 1 Puger. The quality of the development handout teaching materials seen from the aspect of validity is included in the very valid category with an average score of 4.5 from media experts and an average score of 4.7 from material experts categorized as very valid. RPP validation assessment obtained a score of 4.8 categorized as very valid. Other instruments that were validated were the handout implementation observation sheet with a score of 4.8 in the very valid category, the student response questionnaire with an average score of 4.8 in the very valid category, and the test sheet with a score of 4.7 in the very valid category. The practical aspect of the Handout was obtained from the results of the observation of the implementation of the Handout with a score of 4.5 in the very practical category and the results of the student response questionnaire with a score of 4.4 in the very practical category. From the aspect of the effectiveness of the teaching materials, the Handout is declared effective from the results of the student test analysis, namely the increase in the value of the pre-test to the post-test using an average N-Gain obtained of 0.78 so that it has a high level of effectiveness. Thus, the ethnomathematical nuances of the Handout teaching materials that were developed were declared to meet the aspects of validity, practicality, and effectiveness.